Effectiveness of photovoice method in improving tuberculosis knowledge, attitude, practice and treatment outcomes among tuberculosis patients in a hospital in Nigeria - Ahmad, Abdulrahman (2017)
Background: Tuberculosis (TB) is a disease of public health importance especially in developing countries and among the low socioeconomic class. It is estimated that TB is second only to HIV/AIDS as the greatest killer worldwide due to a single infectious agent. In 2013 alone, 9 million people were infected with TB, and 1.5 million died from the disease. Over 95% of TB deaths occur in low- and middle-income countries, and it is among the top 5 causes of death for women aged 15 to 44 years. Knowledge of TB is shown to correlate with a positive attitude and better preventive practices towards the disease. However, knowledge of the disease is shown to be low among different populations, particularly in African populations. Among West African nations, Nigeria reported the lowest knowledge levels of TB. The lack of awareness may lead to subsequent exposures to the risk factors of TB, which would result in an increased number of TB patients who in turn will infect other people. This results in more poverty and ignorance thereby completing the cycle of ignorance, disease, and poverty. This vicious cycle will continue if there is inadequate knowledge, attitude, and practice regarding the disease. Objective: To develop, implement, and evaluate the effectiveness of photovoice health education method in improving TB knowledge, attitude, practice, self-efficacy, and treatment outcome among TB patients in Specialist Hospital Sokoto, Nigeria. Methodology: This study was a two armed double-blind randomized controlled trial. The trial was conducted in two phases; phase 1 was the development of the photovoice intervention using social cognitive theory, which involved recruitment of volunteers, training, and recording of the photovoice video, and phase 2 was the randomized control trial. Two hundred (the calculated sample size n=200) newly diagnosed TB patients were recruited for the study all from one center and randomly allocated to intervention and control arms on a one to one ratio. Only one person facilitated throughout, self-administered validated questionnaire and case report forms were used to record data for the study. The intervention group was exposed to the photovoice video on day one of TB treatment and again at the eighth week after the commencement of anti-TB medications. The control group was exposed to usual TB care and HIV health education on day one and the eighth week after the commencement of anti-TB drugs. Photovoice method in this study is a recorded video showing successfully treated TB patients educating and motivating newly diagnosed TB patients. Outcome data were collected at baseline, immediately post-intervention, two months and six months post-intervention. Outcome measures included: TB knowledge, attitude, practice, self-efficacy and treatment outcomes. Results: Two hundred newly diagnosed TB patients agreed to participate in the study. One hundred and seventy-two (172) participants remained until the end of the study, 92 in the intervention group and 80 in the control group. Analysis of the data showed there was no statistically significant difference in the participants’ baseline data between intervention and control groups. However, photovoice group had higher mean knowledge score (p <0.001) compared with the control group. Photovoice group had higher mean attitude score (p <0.001) compared with the control group. Photovoice group had higher mean practices score (p <0.001) compared with the control group. Moreover, photovoice participants had a higher mean self-efficacy score (p < 0.001) compared with the control group. Similarly, photovoice group have 3 times the odds of successful treatment outcome compared with the control group (p-value = 0.019).Conclusion: Photovoice method is an effective intervention tool for use to improve knowledge, attitude, practice, self-efficacy, and TB treatment outcomes (successful vs unsuccessful) among the newly diagnosed TB patients.